KILOVOLTMETER FOR X-RAY EQUIPMENT - Elmurotova Dilnoza Baxtiyorovna; Tursunbayev Qobiljon Nigmatullayevich; Meyliyev Laziz Orziqulovich (Journals Park Publishing, 2022)
The paper considers a simplified form of kilovoltmeter, where its design is studied. It is shown that this kilovoltmeter contains two semiconductor silicon radiation detectors, which are not sensitive to light.
Keywords: X-ray engineering, kilovoltmeter, receiver, silicon